THE EFFECT OF DIFFERENCES IN ARTIFICIAL BAIT COLOR AND SOAKING TIME IN HAND-LINE FISHING GEAR ON TUNAS (E. afinnis) IN SENDANG BIRU WATERS, MALANG, INDONESIA - Nadia Elis Febrita; Aristi Dian Purnama Fitri; Kukuh Eko Prihantoko (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2021)
Hand-line fishing gear is traditionally used by fishermen in Sendang Biru, Malang, Indonesia to catch Euthynnus affinis. Therefore, this study aims to analyze the color differences of the artificial bait and soak time of E. afinnis's catch. The study was conducted in the waters of Sendang Biru, Malang, Indonesia from July to August 2019, with the experimental fishing method by comparing the artificial bait color variables (white, red, blue, and gray) and soaking time (2 and 20 minutes). The results showed that the artificial red bait color gave the most catches and was affected by the soaking time (with a significant level of 0.05).